EVALUASI STRATEGI BERSAING DALAM INDUSTRI HOTEL STUDI PADA HOTEL SOFYAN BETAWI - Wiwik Rachmarwi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
Tourism is one of the leading sectors in supporting Indonesia's economic recovery. In an effort to improve the quality of tourism facilities and infrastructure necessary to support the accommodation of those activities. One of them is the hospitality industry. Betawi Sofyan Hotel as one of the hotel sharia cannot avoid away from competition three star hotel in Jakarta. Competition hotel makes Hotel Sofyan must have a good strategy to compete with other hotels. Betawi Sofyan Hotel also must analyze the external and internal environment, determine the competitive position in the industry, and formulate a strategy for success in the competition. The results of this study indicate that the Hotel Sofyan has a big opportunity to grow and compete. From a generic analysis that has been done, Betawi Sofyan Hotel has a differentiation strategy and SWOT analysis of the strategy showed that strategy which is suited for aggressive growth policy (Oriented Growth Strategy). Key Success Factor of Betawi Sofyan Hotel are the working spirit (the spirit of motivation) and competence, utilization and capital allocation appropriately used to repair and improve the quality of all facilities available and Corporate Culture Establishment, Implementation Services and Products Character, Improve Brand Equity.